As the wicked watch [large type] - Hall, Tamron; Taylor, T. Shawn (Hall, Tamron. Jordan Manning novel, 2021)
After moving from Texas to Chicago, crime reporter Jordan Manning becomes frustrated with the lack of coverage of a series of murders of black women and does everything she can to give the story the attention it desperately requires.